Prediction of Iranian EFL Learners’ Satisfaction with Online Education through the Dimensions of Online Education: A Gender-based Mixed-Method Study - Shahisavandi, Gholam Hossein (LANGUAGE ART, 2023)
The current study employed a mixed-method approach to investigate the most influential dimensions of online education on Iranian EFL male and female learners’ satisfaction with online education. To this end, 183 EFL learners (96 females and 87 males) studying English at language institutes with the age range from 16 to 25 were selected through convenience sampling. The Learners’ Satisfaction with Online Education Questionnaire designed by Stefanovic et al. (2011), and semi-structured interviews were employed to collect the data. The results of multiple regression analysis demonstrated that three dimensions of online education (instructor, course, and technology) predicted EFL male learners’ satisfaction, and all four dimensions of online education (instructor, course, technology, and environment) could significantly predict females’ satisfaction with online education. It was also revealed that the instructor was the most influential dimension of learners’ satisfaction with online education for both male and female participants. The qualitative results also showed that male and female learners considered the instructor as the most important factor influencing their satisfaction with online education.